Intratumoral immunotherapy of murine pheochromocytoma shows no age-dependent differences in its efficacy - Uher, Ondrej; Hadrava Vanova, Katerina; Lencova, Radka; Frejlachova, Andrea; Wang, Herui; Zhuang, Zhengping; Zenka, Jan; Pacak, Karel (Frontiers in Endocrinology, 2023)
Cancer immunotherapy has shown remarkable clinical progress in recent years. Although age is one of the biggest leading risk factors for cancer development and older adults represent a majority of cancer patients, only a few new cancer immunotherapeutic interventions have been preclinically tested in aged animals. Thus, the lack of preclinical studies focused on age-dependent effect during cancer immunotherapy could lead to different therapeutic outcomes in young and aged animals and future modifications of human clinical trials. Here, we compare the efficacy of previously developed and tested intratumoral immunotherapy, based on the combination of polysaccharide mannan, TLR ligands, and anti-CD40 antibody (MBTA immunotherapy), in young (6 weeks) and aged (71 weeks) mice bearing pheochromocytoma (PHEO). The presented results point out that despite faster growth of PHEO in aged mice MBTA intratumoral immunotherapy is effective approach without age dependence and could be one of the possible therapeutic interventions to enhance immune response to pheochromocytoma and perhaps other tumor types in aged and young host.